The Mediating Role of Motivation to Teach in Burnout Levels and Attitudes toward the Teaching Profession of Prospective Teachers - Dikmen, Melih; Şahin, Aykut; Karakaya, Yunus Emre (My University, 2023)
This study aims to reveal the relationship between burnout levels, attitudes toward the teaching profession, and motivation to teach in prospective physical education and sports teaching. Accordingly, the mediating role of motivation to teach in the relationship between burnout levels and attitudes toward the teaching profession of prospective teachers was investigated. The data of the study were collected online from 685 prospective teachers who studied in the field of sports education in 12 state universities in Turkey. The data were collected by using “Burnout,” Attitudes toward Teaching Profession,” and “Motivation to Teach” scales. Path analyses were conducted to test the direct prediction power of burnout and motivation to teach on the attitudes toward the teaching profession and the indirect prediction power of burnout on attitudes toward the teaching profession through motivation to teach. In conclusion, it was determined that burnout negatively predicted attitude toward the teaching profession and motivation to teach in a significant way, while motivation to teach predicted attitude toward the teaching profession positively in a significant way. Furthermore, it was determined that the negative effect of burnout on the attitude toward the teaching profession was reduced by the mediating role of motivation to teach.
Keywords: Burnout; physical education; motivation to teach; Attitude toward profession; prospective teacher.